A low-cost reinforcement procedure improves short-term weight loss outcomes - Petry, Nancy M. (2011)
PURPOSE: Reinforcement-based treatments, based on behavioral economics models, can improve outcomes of medical conditions with behavioral components. This study evaluated the efficacy of a low-cost reinforcement intervention to produce initial weight loss. METHODS: Overweight individuals (N=56) were randomized to one of two 12-week treatments: LEARN manual with supportive counseling, or that same treatment with opportunities to win $1-$100 prizes for losing weight and completing weight-loss activities. RESULTS: Patients receiving reinforcement lost significantly more weight (6.0%±4.9% baseline bodyweight) than patients in the non-reinforcement condition (3.5%±4.1%; p=0.04). Moreover, 64.3% of patients receiving reinforcement achieved weight loss of ≥ 5% baseline bodyweight versus 25.0% of those in the non-reinforcement condition (p=0.003). Proportional weight lost was significantly related to reductions in total cholesterol and 24-hour ambulatory heart rate. CONCLUSIONS: This reinforcement-based intervention substantially enhances short-term weight loss, and reductions in weight are associated with important changes in clinical biomarkers. Larger-scale evaluation of reinforcement-based treatments for weight loss are warranted.